Highway and Traffic Engineering Intervention Workshop 2023 / Shahreena Melati Rhasbudin Shah … [et al.] - Rhasbudin Shah, Shahreena Melati; Abd Rahman, Zanariah; Keria, Roziah; Dollah, Zuraisah; Md Nor, Noorsuhada; Md Hasan, Ahmad Syauqi (Unit Penerbitan PKAPP, 2024)
Due to the Movement Control Order (MCO) in 2020 and 2021, courses involving laboratories, such as Highway dan Traffic Engineering (CEG552) have been shifted to an Online Distance Learning (ODL) medium, preventing students from gaining hands-on experience with laboratory equipment. Therefore, the Highway and Traffic Engineering Intervention Workshop 2023 program was held on May 19, 2023, in collaboration between “Skuad Motivasi & Pembangunan Pelajar” and the respective Highway and Traffic Engineering lecturers as a platform to assist Bachelor of Engineering (Hons.) Civil (Infrastructure) - EC221 students in improving their PO5 (Modern tool usage). This is the second time around events, the previous one was held on May 19 – 20, 2022. The primary goal of this workshop is to give exposure to final-year students on how to use highway laboratory equipment in an experiment with road materials and pavement surface conditions. This program is one of the faculty's intervention programs designed to meet EAC accreditation requirements and guarantee that EC221 students have adequate experience.